1989
DOI: 10.1007/bf00916758
|View full text |Cite
|
Sign up to set email alerts
|

In vivo andin vitro HeNe laser effects on phagocyte functions

Abstract: The goal of this work was to evaluate the effect of helium-neon (HeNe) laser irradiation on immunocompetent cells. We used the in vivo skin window method and in vitro granulocyte function tests. The study of cellular migration showed a marked decrease in vitro and in vivo in a dose-independent manner. Superoxide release was not modified by laser irradiation. The granulocyte's aggregation, when using PHA and PMA, presented a reduction that was statistically very significant, not as a subordinate dose. An increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
5

Year Published

1992
1992
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
1
0
5
Order By: Relevance
“…Basford [13] reportou aumentos de temperatura tão pequenos como 0,1 a 0,5 graus Celsius, Karu [16] usando 3 W.m -2 de intensidade encontrou aumento da temperatura média de 10 -3 graus C. Um aumento na temperatura de 0,4 a 0,6 graus C, na pele irradiada por um diodo laser GaAs de 850 nm e 70 mW, também foi referido por Boussignac et al [16]. No trabalho de Ricevuti confirma-se que os efeitos da irradiação laser são termais e não correlacionados com as modificações da estrutura da glicoproteína de membrana que possui funções receptivas [39].…”
Section: Que Efeitos Produzem Os Laseres Nos Tecidos?unclassified
See 1 more Smart Citation
“…Basford [13] reportou aumentos de temperatura tão pequenos como 0,1 a 0,5 graus Celsius, Karu [16] usando 3 W.m -2 de intensidade encontrou aumento da temperatura média de 10 -3 graus C. Um aumento na temperatura de 0,4 a 0,6 graus C, na pele irradiada por um diodo laser GaAs de 850 nm e 70 mW, também foi referido por Boussignac et al [16]. No trabalho de Ricevuti confirma-se que os efeitos da irradiação laser são termais e não correlacionados com as modificações da estrutura da glicoproteína de membrana que possui funções receptivas [39].…”
Section: Que Efeitos Produzem Os Laseres Nos Tecidos?unclassified
“…O sistema de membrana NADPH permanece intacto, o que explica os dados normais de produção e liberação de radicais livres. Em resumo, os efeitos biológicos induzidos pelo laser estão correlacionados a uma ação sobre a polarização da membrana e a um efeito sobre o centrossoma [39].…”
Section: Tipos De Efeitos Produzidos Pelo Laser De Baixa Intensidadeunclassified
“…Les effets b6n6-fiques des rayons laser He-Ne nM 630 de faible 6nergie sur les spermatozo~des se limiteraientils au syst~me de FIV murin, ou pourraient-ils aussi s'4tendre aux procr4ations m4dicalement assist4es humaines, am41iorant les performances reproductives des spermatozoides. Mais il faudrait d'abord s'assurer chez l'homme de l'innocuit6 ~ petite dose de cette irradiation que l'on sait ~tre d416t~re ~ dose 61ev4e [29]. …”
Section: R S L Eunclassified
“…Comme en t6moignent plusieurs 6tudes faites avec les rayons ultraviolets [34] sur des lymphocytes, avec les rayons gamma [11,23] ou avec les ondes 61ectromagn6tiques de fr6quences radio [12] sur des spermatozoYdes de souris, l'irradiation intense et prolong6e est dangereuse. L'irradiation de lym- phocytes et de granulocytes au laser He-Ne est ~galement nocive [29] lorsqu'elle est intense et prolong~e. Par contre, l'irradiation laser He-Ne de faible ~nergie (LFE) a ~t~ b~n~fique sur diverses lign~es de cellules somatiques, de spermatozo~des et de cellules embryonnaires [25].…”
Section: Introductionunclassified
“…Moreover, Ricevuti et al [5] described the effect of helium-neon (He-Ne) laser irradiation on immunocompetent cells using the in vivo skin window method and the in vitro granulocyte function tests. They showed that cellular migration was markedly decreased by laser irradiation both in vivo and in vitro in a dose-independent manner, and that the laser irradiation produced no changes in random migration or in chemotaxis.…”
Section: Introductionmentioning
confidence: 99%